Flexible and broadband colloidal quantum dots photodiode array for pixel-level X-ray to near-infrared image fusion - Jing Liu; Peilin Liu; Tailong Shi; Mo Ke; Kao Xiong; Yuxuan Liu; Long Chen; Linxiang Zhang; Xinyi Liang; Hao Li; Shuaicheng Lu; Xinzheng Lan; et al. (Nature Communications, 2023)
Abstract Combining information from multispectral images into a fused image is informative and beneficial for human or machine perception. Currently, multiple photodetectors with different response bands are used, which require complicated algorithms and systems to solve the pixel and position mismatch problem. An ideal solution would be pixel-level multispectral image fusion, which involves multispectral image using the same photodetector and circumventing the mismatch problem. Here we presented the potential of pixel-level multispectral image fusion utilizing colloidal quantum dots photodiode array, with a broadband response range from X-ray to near infrared and excellent tolerance for bending and X-ray irradiation. The colloidal quantum dots photodiode array showed a specific detectivity exceeding 1012 Jones in visible and near infrared range and a favorable volume sensitivity of approximately 2 × 105 μC Gy−1 cm−3 for X-ray irradiation. To showcase the advantages of pixel-level multispectral image fusion, we imaged a capsule enfolding an iron wire and soft plastic, successfully revealing internal information through an X-ray to near infrared fused image.